Detecting micro- and nanoscale variations in element mobility in high-grade metamorphic rocks: Implication for precise U-Pb dating of zircon - Kusiak, M.; Wilde, Simon; Wirth, R.; Whitehouse, M.; Dunkley, Daniel; Lyon, I.; Reddy, Steven; Berry, A.; De Jonge, M. (2017)
© 2018 American Geophysical Union. Reliable geochronology is fundamental to our understanding of planetary evolution and the geological events that have shaped the Earth. Zircon has a robust crystal structure and is a key mineral in geochronological studies because it incorporates small amounts of actinides during growth. Currently, the best physical evidence for the presence of differentiated crust in the first 500 million years of the Earth’s history comes from intra-grain isotopic microanalysis of zircon crystals. However, it has been long recognized that isotope systematics in zircon can show great complexity, not only from the presence of multiple stages of growth in single grains, but also from disturbance of accumulated radiogenic Pb during subsequent geological events. Although geochronologists are aware of the problem of Pb mobilization during metamorphism, the nature of mobilization on a submicron scale is not entirely understood, especially where evidence has emerged of inhomogeneity and unsupported radiogenic Pb migration. The recent discovery of nanospheres of metallic radiogenic Pb in zircon from granulites explains, in part, instances of reversely discordant age measurements and irregular counts on Pb isotopes during analysis by secondary ion mass spectrometry (SIMS). Studies are continuing to reveal the nature of Pb nanospheres, so that possible mechanisms and conditions requisite for their formation can be proposed for testing by future investigations.